Biodiesel as an Alternate Energy Resource: A Study - Gupta, Vipul; Saksham; Kumar, Santosh; Kumar, Rakesh (Asian Review of Mechanical Engineering, 2020)
As the world has been lately relied upon non-renewable fossil fuels for its daily energy requirements. Their depletion rate has been increased alarmingly, so there is a need to find an alternative energy source which can prove as a good alternative. From the many available sources, biodiesel has emerged as one of the best sources available. The reasons being included properties like it is highly biodegradable, non-toxic and has almost zero emissions. Distinct edible and non-edible oils such as coconut oil, castor oil, mahua, rice bran oil, apricot, jatropha, curcas, karanja and cotton seed oil, eucalyptus oil can be utilized to produce biodiesel. It has a potential to replace existing fuels, like diesel and petrol in many applications. This paper includes a detailed review on different aspects related to biodiesel. This includes properties, merits, demerits, extraction, and production techniques of biodiesel. In addition, future scopes of the biodiesel are also discussed in this paper.